2010
DOI: 10.1002/ijc.25167
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐breast cancer potential of SS1020, a novel antiestrogen lacking estrogenic and genotoxic actions

Abstract: Long-term treatment with tamoxifen (TAM) increases the risk of developing endometrial cancer in women. Several antiestrogens developed in last decades have been discontinued from clinical testing because of their undesirable effects on the uterus. To avoid such serious side-effect while increasing the drug's anti-breast cancer potential, new triphenylethylene antiestrogens, 2E-3-{4-[(E)-4-chloro-1-(4-hydroxyphenyl)-2-phenylbut-1-enyl]-phenyl} acrylic acid (SS1020) and 2E-3-{4-[(Z)-4-chloro-1,2-diphenylbut-1-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…In our previous papers (Laxmi et al, 2010;Suzuki et al, 2011), DMBA-induced mammary tumors were confirmed by pathological examination. The sections of the mammary tumors were deparaffinized in xylene and processed routinely and stained with hematoxylin and eosin.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…In our previous papers (Laxmi et al, 2010;Suzuki et al, 2011), DMBA-induced mammary tumors were confirmed by pathological examination. The sections of the mammary tumors were deparaffinized in xylene and processed routinely and stained with hematoxylin and eosin.…”
Section: Resultsmentioning
confidence: 85%
“…Rats were given water and a phytoestrogen-free AIN-76A diet food and kept on a 12 h light/dark cycle throughout the study. Mammary carcinoma (~8 mm diameter tumor) was induced by treating rats (Sprague-Dawley, 8-week-old females) with a single oral dose (50 mg/kg) of DMBA, following the established protocol (Toko et al, 1995;Yamamoto et al, 2005;Laxmi et al, 2010;Suzuki et al, 2011). The rats (5 rats/dose) were then treated orally for 3 weeks with daidzein (0.69 or 6.9 mg/kg/day), equol (0.65 mg/kg/day), genistein (0.73 mg/kg/day), or TAM (1.0 mg/kg/day) at a dose molar equivalent to TAM [1.0 mg (2.7 μmol)/kg or 10 mg (27 μmol)/kg/day].…”
Section: Dmba-induced Rat Mammary Carcinoma Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…31,32 Several novel SERMs have been synthesized and evaluated for their potential to improve breast cancer treatment with reduced adverse effect profile compared to the gold-standard TAM. [33][34][35] Collectively, the results of these studies demonstrate that the CYP2D6-generated 4-OH metabolites of TAM represent a much higher percentage of total plasma exposure with TAM treatment, and at many-fold greater estrogenic and antiestrogenic activity, these active TAM metabolites are likely to measurably contribute to the clinical efficacy and safety profile of TAM in women with breast cancer. Adjusted for dose, the plasma concentrations of TOR and metabolites reported in our study are consistent with the values for the 60 mg clinical dose reported in previous studies.…”
mentioning
confidence: 84%